The Urban Maps and Plans of Joseph Bouchette, Surveyor General of Lower Canada 1804 to 1841 - Ferley, Paul (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1999)
This paper examines the urban maps and plans published by Joseph Bouchette, Surveyor General of Lower Canada, from 1804 to 1841. It employs the approach advocated by such analysts as J.B Harley that maps not be regarded exclusively as a "mirror" but also as a "text." The former, more restrictive, approach demands that maps should reflect the most current information available of the region depicted, a requirement that Bouchette's urban maps did not always meet. However, using the latter approach, Bouchette's maps illustrate the various socio-economic forces prevalent in the first half of the 19th century that had an impact on urban areas in British North America. As well, the failure by Bouchette to include the most recent developments in his urban maps can be viewed as reflecting the priorities and interests of the colonial authorities. These interests seemed to place a greater priority on detailing the topography and political boundaries of the surrounding hinterland as opposed to conveying information on existing urban areas.